2007
DOI: 10.1002/rra.1029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river discharge on abundance and instantaneous growth of age‐0 carpsuckers in the Oconee River, Georgia, USA

Abstract: The Oconee River in middle Georgia, U.S.A., has been regulated by the Sinclair Dam since 1953. Since then, the habitat of the lower Oconee River has been altered and the river has become more incised. The altered environmental conditions of the Oconee River may limit the success of various fish populations. Some obligate riverine fishes may be good indicator species for assessing river system integrity because they are intolerant to unfavourable conditions. For example, many sucker species require clean gravel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Broadly, and consistent with other research (Propst & Gido, 2004;King, Tonkin & Mahoney, 2009;Tan et al, 2010), native fish densities were highest at all sites in years with above average discharge. However, other aspects of flow regime such as timing (Bednarski, Miller & Scarnecchia, 2008) and stability of flows (Freeman et al, 2001;Peterson & Jennings, 2007) are also known to favour recruitment of stream fishes. Because these variables were highly correlated with mean annual discharge, we were unable to segregate the relative influence of each factor.…”
Section: Discussionsupporting
confidence: 92%
“…Broadly, and consistent with other research (Propst & Gido, 2004;King, Tonkin & Mahoney, 2009;Tan et al, 2010), native fish densities were highest at all sites in years with above average discharge. However, other aspects of flow regime such as timing (Bednarski, Miller & Scarnecchia, 2008) and stability of flows (Freeman et al, 2001;Peterson & Jennings, 2007) are also known to favour recruitment of stream fishes. Because these variables were highly correlated with mean annual discharge, we were unable to segregate the relative influence of each factor.…”
Section: Discussionsupporting
confidence: 92%
“…For example, fully assessing the role of hydrologic variation on a given population may require determining flow-ecology relationships at multiple temporal scales. Sub-daily flow variation may influence short-term habitat use (Schwartz and Herricks, 2005), migration (Carmichael et al, 1998), feeding ability (Barwick and Hudson, 1985) and spawning success (Grabowski and Isely, 2007), while habitat creation (Trush et al, 2000), growth (Peterson and Jennings, 2007), and recruitment (Rulifson and Manooch, 1990) may be influenced by hydrologic variation at seasonal or annual scales. Cumulative frequency plots like those presented here represent the distribution of each hydrologic metric calculated for each day, rather than daily statistics for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Although discharge did not explain a high proportion of the variation in year‐class strength, all relationships (expect for one) were negative. Peterson and Jennings () found that long periods of high discharge were inversely related to year‐class strength of Carpiodes spp. in the Oconee River, Georgia.…”
Section: Discussionmentioning
confidence: 99%
“…Freeman et al (2001) reported that high densities of age-0 catostomids in the Tallapoosa River, Alabama, were positively associated with persistence of shallow-water habitat in summer. As such, Peterson and Jennings (2007) argued that poor recruitment of age-0 Carpiodes spp. was due to reduced availability of shallow-water habitats during high flows.…”
Section: Discussionmentioning
confidence: 99%